Introducing Neural Networks as a Computational Intelligent Technique - Azizi, Aydin; Entessari, Farshid; Osgouie, Kambiz Ghaemi; Rashnoodi, Amirhossein Rezaei (Trans Tech Publications Ltd, 2014)
Neural networks have been applied very successfully in the identification and control of dynamic systems. The universal approximation capabilities of the multilayer perceptron have made it a popular choice for modeling nonlinear systems and for implementing general-purpose nonlinear controllers. In this paper we try to model and control the mass-spring-damper mechanism as a 1 DOF system using neural networks. The control architecture used in this paper is Model reference controller (MRC) as one of the popular neural network control architectures.
International Conference on Intelligent Materials and Mechatronics (IMM 2013) -- NOV 01-02, 2013 -- Hong Kong, PEOPLES R CHINA
Keywords: Neural networks; Dynamic systems; Function approximation; Control; Mass-spring-damper mechanism; MRC